Shedding Light on the Active Species in a Cobalt‐Based Covalent Organic Framework for the Electrochemical Oxygen Evolution Reaction - Pouya Hosseini; Andrés Rodríguez‐Camargo; Yiqun Jiang; Siyuan Zhang; Christina Scheu; Liang Yao; Bettina V. Lotsch; Kristina Tschulik (Advanced Science)
Abstract While considerable efforts have been devoted to developing functionalized covalent organic frameworks (COFs) as oxygen evolution electrocatalysts in recent years, studies related to the investigation of the true catalytically active species for the oxygen evolution reaction (OER) remain lacking in the field. In this work, the active species of a cobalt‐functionalized COF (TpBpy‐Co) is studied as electrochemical OER catalyst through a series of electrochemical measurements and post‐electrolysis characterizations. These results suggest that cobalt oxide‐based nanoparticles are formed in TpBpy‐Co from Co(II) ions coordinated to the COF backbone when exposing TpBpy‐Co to alkaline media, and these newly formed nanoparticles serve as the primary active species for oxygen evolution. The study thus emphasizes that caution is warranted when assessing the catalytic activity of COF electrocatalysts, as the pristine COF may act as the pre‐catalyst, with the active species forming only under catalyst operating conditions. Specifically, strong coordination between COFs and metal centers under electrochemical operation conditions is crucial to avoid unintended transformation of COF electrocatalysts. This work thus contributes to the rational development of earth‐abundant COF OER catalysts for the production of green hydrogen from renewable resources.